Examination of the Relationship Between Economic Growth and Research and Development Expenditures in Azerbaijan, Kazakhstan and Kyrgyzstan - N. Huseynli (Финансы: теория и практика)
The article is devoted to topical issues related to the impact of investment in research and development (R&D) on the acceleration of economic growth on the example of Azerbaijan, Kazakhstan, and Kyrgyzstan. All three countries need to modernize and diversify their economies, especially in the context of unstable conditions in the world fuel and raw materials markets and the trend towards decarbonization of the world economy. The relationship between economic growth and R&D expenditures was studied through econometric analysis (Granger test), which increases the accuracy and reliability of the results. The relationship between R&D and economic growth is examined using the annual GDP data of the respective countries and the ratio of R&D expenditures to GDP for the period 2005–2018. The data were analysed using EViews statistical package. It was found that GDP growth in Kyrgyzstan is the reason for cost increases on research and development. At the same time, a causal relationship was not found in Azerbaijan or Kazakhstan. According to the results of the correlation analysis, there is a very high positive correlation (0.92) between the growth data given in Azerbaijan and R&D expenditures. However, in Kyrgyzstan (–0.69) and Kazakhstan (–0.33), on the contrary, there is a moderate relationship in the negative direction. It is concluded that one of the ways to increase economic growth in the long term is to investment in R&D. The results of the research can be used by official institutions to assess the economic profiles of the countries under consideration and in the real sector of the economy.